2019
DOI: 10.1159/000499307
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Sacral Neuromodulation on Sexual Dysfunction

Abstract: Background/Aims: Sacral neuromodulation (SNM) is a well-established treatment in several urinary and bowel dysfunctions, nevertheless its role on sexual dysfunction remains unclear. We evaluate the impact of SNM on sexual function and its association with age at SNM, functional diagnosis and post-void residual urine (PVR) before SNM. Methods: Patients who had SNM were retrospectively analyzed. Sexual function was assessed before and after treatment with the International Index of Erectile Function (IIEF-5) for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…Age and functional diagnosis showed weak correlation (Table 3 and 5). Regarding age and PVR our results were similar to Oliveira et al 25 but defer in FSFI and functional diagnosis which showed significant correlation in their results. Interestingly, we found significant correlation between age and FSFI domains vaginal lubrication and pain, and also between PVR and pain.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Age and functional diagnosis showed weak correlation (Table 3 and 5). Regarding age and PVR our results were similar to Oliveira et al 25 but defer in FSFI and functional diagnosis which showed significant correlation in their results. Interestingly, we found significant correlation between age and FSFI domains vaginal lubrication and pain, and also between PVR and pain.…”
Section: Discussionsupporting
confidence: 90%
“…Similarly, Zabihi et al 24 reported a 53% improvement in all FSFI domain scores except for desire and pain. also, Oliveira et al 25 showed some improvement in all domains, but only lubrication showed statistically significant improvement. Banakhar et al 9 reported significant improvement in total FSFI and desire and orgasm domains.…”
Section: Discussionmentioning
confidence: 83%
“…The Food and Drug Administration (FDA) has approved SNM for treating overactive bladder, non-obstructive urinary retention, and bowel dysfunction, and other non-FDA approved indications include chronic pelvic pain and bladder pain syndrome [12][13][14] SNM has a positive impact on ejaculatory function compared to alpha-blockers and bladder neck incision [15,16].…”
Section: Discussionmentioning
confidence: 99%
“…There is, however, evidence of SNM being useful in patients with interstitial cystitis and chronic pelvic pain, and recent studies demonstrate that in patients receiving SNM for urinary and bowel dysfunction, a significant improvement in sexual function, measured by both International Index of Erectile Function (IIEF-5) and Female Sexual Function Index (FSFI) scores, was experienced by both male and female patients. 18,19 It is likely we will see a broadening in the scope of SNM use in the near future.…”
Section: Future Of Sacral Neuromodulationmentioning
confidence: 99%